PENGARUH UKURAN PERUSAHAAN, UKURAN KAP, DAN LEVERAGE TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020 – 2022 - Alfa Durri Khayya; Kasidi; Rita Andini; Marsiska Ariesta Putri (Jurnal Ilmiah Ekonomika & Sains, 2025)
This study aims to analyze the effect of company size, Public Accounting Firm (KAP) size, and leverage on audit report lag in financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The sampling technique used was purposive sampling with a sample size of 92 companies (276 observations). Data were analyzed using logistic regression. The results showed that company size had a significant effect on audit report lag, while KAP size and leverage did not have a significant effect. The coefficient of determination showed that the independent variables only explained 6.6% of the variation in audit report lag, while the rest was influenced by other variables outside the model.